Childhood socioeconomic status and the pace of structural neurodevelopment: accelerated, delayed, or simply different? - Rakesh, Divyangana; Whittle, Sarah; Sheridan, Margaret A.; McLaughlin, Katie A. (Trends in cognitive sciences, 2023)
Theories make contrasting predictions about whether adverse experiences and low socioeconomic status (SES) are associated with accelerated or delayed neurodevelopment.Existing evidence is more consistent with low SES predicting delayed rather than accelerated brain development. However, no existing model fully captures observed differences between low- and high-SES adolescence.Low SES and other adverse environments are likely associated with brain developmental trajectories that differ in multiple ways considering the available evidence.We suggest that low SES is associated with brain maturation patterns characterized by lower volume and slower rates of change throughout development.Longitudinal research, especially in the early years, is needed to rigorously test how adversity and SES are associated with deviations from typical developmental trajectories. Socioeconomic status (SES) is associated with children’s brain and behavioral development. Several theories propose that early experiences of adversity or low SES can alter the pace of neurodevelopment during childhood and adolescence. These theories make contrasting predictions about whether adverse experiences and low SES are associated with accelerated or delayed neurodevelopment. We contextualize these predictions within the context of normative development of cortical and subcortical structure and review existing evidence on SES and structural brain development to adjudicate between competing hypotheses. Although none of these theories are fully consistent with observed SES-related differences in brain development, existing evidence suggests that low SES is associated with brain structure trajectories more consistent with a delayed or simply different developmental pattern than an acceleration in neurodevelopment.